Dietary adaptation mechanisms to climate change-driven changes in micronutrients in wheat and other cereals - CGIAR Research Program on Wheat (2021)
Climate-change impacts on nutrient levels in staple grains (focus on iron, zinc) could negatively impact mineral deficiencies amongst at-risk populations. Potential dietary-adaptation strategies include replacing refined by whole grains.